2022
DOI: 10.3390/antiox11030458
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of the Role of Secondary Metabolites for Mitigation of Acid Soil Stress in Cereals Using Dehydroascorbate and Mono-Dehydroascorbate Reductases

Abstract: The present study investigates the potential ameliorative role of seven secondary metabolites, viz., ascorbate (AsA), reduced glutathione (GSH), jasmonic acid (JA), salicylic acid (SA), serotonin (5-HT), indole–3–acetic acid (IAA) and gibberellic acid (GA3), for mitigation of aluminium (Al3+) and manganese (Mn2+) stress associated with acidic soils in rice, maize and wheat. The dehydroascorbate reductase (DHAR) and mono-dehydroascorbate reductase (MDHAR) of the cereals were used as model targets, and the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Of late, we have used molecular docking tools to predict the possible interactions of metal/metalloid ions with such targets of different plants [ 48 , 49 , 50 , 51 ]. In the present study, in vitro analysis revealed that As 3+ may affect the antioxidant system of rice, and thus, it was thought prudent to perform an in silico analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of late, we have used molecular docking tools to predict the possible interactions of metal/metalloid ions with such targets of different plants [ 48 , 49 , 50 , 51 ]. In the present study, in vitro analysis revealed that As 3+ may affect the antioxidant system of rice, and thus, it was thought prudent to perform an in silico analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The other docking parameters were the same as that of the Mn-SOD. The five best-docked poses of all the ligands, in terms of docking score, were considered for further analysis, following the methodology provided by Choudhury et al [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…), attack by weeds, and insects, as well as by abiotic components also ( Moulick et al, 2018d ; Ghosh et al., 2020a ; Ghosh et al., 2020b ; Ghosh et al., 2021 ; Ghosh et al., 2022a ; Ghosh et al., 2022b ; Mateos Fernández et al., 2022 ; Tonnang et al., 2022 ; Jain et al., 2022a ; Jain et al., 2022b ). Among the abiotic stress including heat and chilling stress ( Aslam et al., 2022 ; Haider et al., 2022 ; Ullah et al., 2022 ; Verma et al., 2022 ), limitation of water (drought), limitation of nutrients, elevated levels of salt, and hazardous/toxic metals and metalloids in the soil ( Hernandez et al., 2000 ; Moulick et al., 2019 ; Saha et al., 2019 ; Sahoo et al., 2019 ; Moulick et al., 2021 ; Choudhury et al., 2022a ; Choudhury et al., 2022b ; Choudhury and Moulick, 2022 ; Mazumder et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Today, among the other constraints present in the agro-environmental system (like heavy metals, salinity, etc.) drought is one of the most devastating abiotic stresses that strongly affect agriculture and threaten global food security [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. The emergence of recurrent droughts has resulted in the desertification of agricultural lands and often rendering it unusable for a prolonged period.…”
Section: Introductionmentioning
confidence: 99%